Elimination‐Fusion Self‐Assembly of a Nanometer‐Scale 72‐Nucleus Silver Cluster Caging a Pair of [EuW10O36]9− Polyoxometalates. Issue 8 (9th January 2018) - Zhang, Shan‐Shan; Su, Hai‐Feng; Wang, Zhi; Wang, Xing‐Po; Chen, Wen‐Xian; Zhao, Quan‐Qin; Tung, Chen‐Ho; Sun, Di; Zheng, Lan‐Sun
Abstract: The largest known polyoxometalate (POM)‐templated silver‐alkynyl cluster, [(EuW10 O36 )2 @Ag72 ( t BuC≡C)48 Cl2 ⋅ 4 BF4 ] (SD/Ag20 ), was isolated under solvothermal conditions and structurally characterized. It was confirmed by single‐crystal X‐ray diffraction (SCXRD) as a EuW10 2 ‐in‐Ag72 clusters‐in‐cluster rod‐like compound. The high‐resolution electrospray ionization mass spectrometry (HR‐ESI‐MS) shows that such a double anion‐templated cluster is assembled from a crucial single anion‐templated Ag42 intermediate in the solution. The crystallization of Ag42 species (SD/Ag21), followed by SCXRD, gave an important clue about the assembly route ofSD/Ag20 in solution: the Ag42 cluster eliminates six silver atoms laterally, then fuses together at the vacant face to form the final Ag72 cluster (elimination‐fusion mechanism). The characteristic emission of [EuW10 O36 ] 9− is well maintained inSD/Ag20 . This work not only provides a new method for the synthesis of larger silver clusters as well as the functional integration of the silver cluster and POMs, but also gives deep insights about the high‐nuclear silver cluster assembly mechanism. Abstract : Cage rage : A 72‐nucleus silver cluster caging a pair of [EuW10 O36 ] 9− polyoxometalates: Structure and elimination‐fusion assembly mechanism resulted in the largest known POM‐templated silver‐alkynyl cluster